The effect of technological, environmental, and individual contexts on CBEG: the role of trust as a mediator - H. S. Alkhilani, Wissam (Little Lion Scientific R&D, 2024)
Cloud-based E-Government (CBEG) offers several advantages to governments. However, the adoption rates of CBEG among institutions of public sectors in developing countries are still limited. The EGovernment development and participation index in Iraq is lower than the regional and global averages. This research seeks to pinpoint the most influential factors affecting the intention to adopt CBEG from the perspectives of technological, individual and environmental contexts in Iraq. Based on relevant theories, this study proposed that technological, environmental and individual factors affect the CBEG. In addition, trust was proposed as a mediator. Data are collected from 366 decision-makers as the target respondents of this study through five institutions responsible for the E-Government project in Iraq. Data analysis was performed with SMART-PLS 4. The findings showed that technological, individual, and environmental variables had statistically significant effects on the adoption of CBEG. Social influence was insignificant. Further, trust mediated the proposed relationships. More focus on technological, environmental, and individual factors will enhance the adoption of CBEG.